Agreement between the Government of the French Republic, the Government of the Kingdom of Belgium, the Government of the Kingdom of the Netherlands and the Government of the United Kingdom of Great Britain and Northern Ireland amending and supplementing the Agreement between the Government of the Kingdom of Belgium, the Government of the French Republic and the Government of the United Kingdom of Great Britain and Northern Ireland, concerning Rail Traffic between Belgium and the United Kingdom using the Channel Fixed Link with Protocol, done at Brussels on 15 December 1993, Brussels, 7 July 2020. ([2020-08-13]) - Unknown
No abstract available